2023
DOI: 10.3390/v15071441
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review on Cardiometabolic Risks and Perinatal Outcomes among Pregnant Women Living with HIV in the Era of Antiretroviral Therapy

Abstract: Antiretroviral therapy (ART) regimens have been shown to cause metabolic changes in people living with HIV (PLWH), predisposing them to cardiometabolic disease (CVMD). However, such evidence is less established in pregnant women living with HIV (pWLWH) on ART. Pregnancy-induced cardiometabolic risks (CMR) can predispose to unfavourable pregnancy outcomes and further persist in the postpartum period, resolve, and recur in subsequent pregnancies, or emerge as newly diagnosed chronic diseases of ageing. Therefore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 84 publications
0
3
0
Order By: Relevance
“…South Africa is currently experiencing a convergence of NCDs and CDs [ 22 , 23 , 24 , 25 , 26 ], causing the burden of multimorbidity to range from 3% to 87% in various group populations. The common multimorbidity patterns in South Africa are combined TB and HIV, hypertension and diabetes, and hypertension and HIV [ 27 ], and to a lesser extent, the coexistence of HIV, anaemia hypertension, and/or diabetes has been reported [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…South Africa is currently experiencing a convergence of NCDs and CDs [ 22 , 23 , 24 , 25 , 26 ], causing the burden of multimorbidity to range from 3% to 87% in various group populations. The common multimorbidity patterns in South Africa are combined TB and HIV, hypertension and diabetes, and hypertension and HIV [ 27 ], and to a lesser extent, the coexistence of HIV, anaemia hypertension, and/or diabetes has been reported [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…While multimorbidity requires a complexity of care [ 13 , 31 , 32 ], most local studies have reported medication adherence from a single index point of view for hypertension, diabetes, and HIV treatments. The era of an anti-retroviral therapy (ART) programme in South Africa has improved the health of people living with HIV (PLWH) but has come along with cardiometabolic diseases [ 26 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation